The role of endothelial cell–pericyte interactions in vascularization and diseases - Gan Li; Junjie Gao; Peng Ding; Youshui Gao (Journal of Advanced Research)
Background: Endothelial cells (ECs) and pericytes (PCs) are crucial components of the vascular system, with ECs lining the inner layer of blood vessels and PCs surrounding capillaries to regulate blood flow and angiogenesis. Intercellular communication between ECs and PCs is vital for the formation, stability, and function of blood vessels. Various signaling pathways, such as the vascular endothelial growth factor/vascular endothelial growth factor receptor pathway and the platelet-derived growth factor-B/platelet-derived growth factor receptor-β pathway, play roles in communication between ECs and PCs. Dysfunctional communication between these cells is associated with various diseases, including vascular diseases, central nervous system disorders, and certain types of cancers. Aim of review: This review aimed to explore the diverse roles of ECs and PCs in the formation and reshaping of blood vessels. This review focused on the essential signaling pathways that facilitate communication between these cells and investigated how disruptions in these pathways may contribute to disease. Additionally, the review explored potential therapeutic targets, future research directions, and innovative approaches, such as investigating the impact of EC-PCs in novel systemic diseases, addressing resistance to antiangiogenic drugs, and developing novel antiangiogenic medications to enhance therapeutic efficacy. Key scientific concepts of review: Disordered EC-PC intercellular signaling plays a role in abnormal blood vessel formation, thus contributing to the progression of various diseases and the development of resistance to antiangiogenic drugs. Therefore, studies on EC-PC intercellular interactions have high clinical relevance.